Angioplasty of the Superior Gluteal Artery in 34 Patients With Buttock Claudication. (June 2014) - Batt, Michel; Baqué, Jean; Ajmia, Florian; Cavalier, Maxime
Purpose: To evaluate the performance of balloon angioplasty in the treatment of superior gluteal artery (SGA) lesions and the factors influencing results. Methods: Between April 1997 and June 2012, 217 patients were treated for disabling buttock claudication. Of these, 34 (15%) consecutive patients (30 men; mean age 70±9 years) underwent angioplasty for 44 SGA origin lesions (5 bilateral): 24 stenoses and 20 occlusions. Standardized follow-up included clinical examination at 1 and 6 months and annually thereafter; angiography or computed tomography was obtained in cases of recurrent buttock claudication. Results: Angioplasty was successful in 31 patients; 3 of the 20 SGA occlusions could not be recanalized. Twenty-four (59%) SGAs were treated without a stent (14 stenoses and 10 occlusions), while 10 stenoses and 7 occlusions were stented. There were no instances of SGA rupture, occlusion, or pseudoaneurysm. Two recanalizations were complicated with contrast extravasation in the buttock without consequence. Over a mean 49.8±39 months (range 1–132), 5 patients died of unrelated causes. Buttock claudication recurred in 13 (38%) patients (14 SGA lesions) at a mean 21.5±14 months (range 1–132); repeat angioplasty was successful in 8 patients. Estimates of primary and secondary freedom from symptom recurrence at 4 years were 60% and 68%, respectively. There was no difference in patency between SGAs treated for occlusion or stenosis or between those treated with or without a stent. Conclusion: In this series, angioplasty has proven to be a safe and efficacious way to treat SGA lesions with disabling claudication. Repeat balloon dilation was effective in treating SGA restenosis but failed in three quarters of the reocclusions. Progress in guidewire design and optimal use has improved success with SGA occlusions.